Suitability of soil types for Paecilomyces lilacinus and Pochonia chlamydosporia and their performance against root-knot nematode, Meloidogyne incognita on Lycopersicon esculentum in glasshouse - NAGESH, M; JAVEED, SALEEM; RAMANUJAM, B; RANGESWARAN, R (The Indian Journal of Agricultural Sciences, 2026)
During 2007-09, five broad soil types, black cotton, red laterite, alluvial, loamy sand and mountain soils collected from Regional Centre, NBSSLUP, Bangalore, were examined for their suitability to NBAII isolates of antagonistic fungi, Paecilomyces lilacinus (Samson) Thomson and Pochonia chlamydosporia (Goddard) Zare, Gams and Evans in terms of their establishment; temporal survival and behaviour; pathogenicity to Meloidogyne incognita (Kofoid and White) Chitw. under glasshouse conditions and to arrive at the baseline data for field guidance. Except black cotton soil, other soil types examined were suitable for tomato root growth, root-knot nematode infection and effective parasitization of the egg masses by the fungi under report. The time-course behaviour of P. lilacinus and P. chlamydosporia in red laterite, alluvial, loamy and mountain soils were more or less similar. Both the fungi established in the first 2-3 weeks in soils tested, increased in number in the next 6-7 weeks with a plateau at 8-10 weeks after application, marginally declined and reached constancy at 12 weeks after application, following more or less a normal curve. Mountain soil with lower pH and higher organic carbon was best suited to both the fungi in terms of egg mass parasitization and propagules multiplication. Better suitability of mountain soil, red laterite and alluvial soils for these fungal establishment, proliferation and pathogenicity to root-knot nematodes in tomato rhizosphere was attributed to high to medium organic carbon status, near neutral pH and equitable soil physical components.